Ideology of Algerian libération Revolution in the november 1st 1954 déclaration : An Analytical study - ouuamane, Houria (The Algerian Historical Journal, 2026)
The Manifesto of November 1, 1954 is considered an integrated program that represents, in its content, a founding document for the modern Algerian state. It is the result of an effort issued by the independent national liberation movement since 1962. From texts and literature, it crystallized, over three decades of time, the libertarian vision and determined the principled positions on internal and external variables locall., regionally, and internationally. It is also considered the first approach that followed the liberation revolution, as it called on the Algerian people and all national segments to unite, Making the national issue the only common denominator, as it is a just issue that concerns everyone, especially free human consciences